Zero-Downtime Migration Strategies for Large-Scale Distributed Services - Tharun Damera (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Zero-downtime migration strategies for large-scale distributed services present significant challenges in maintaining system reliability and user satisfaction. This comprehensive article explores various approaches including progressive traffic shifting, blue-green deployments, and canary releases, focusing on their implementation in modern cloud-native environments. The article examines critical aspects such as data consistency mechanisms, service mesh architectures, automated rollback systems, and orchestrated deployment pipelines. Through detailed investigation of real-world implementations, this article demonstrates how organizations can achieve seamless migrations while maintaining service availability across distributed environments. The article highlights the importance of comprehensive monitoring, automated testing, and sophisticated failure detection systems in ensuring successful migrations across complex infrastructure landscapes.